Multi-level storage and ultra-high speed of superlattice-like Ge50Te50/Ge8Sb92 thin film for phase-change memory application. (12th September 2017) - Wu, Weihua; Chen, Shiyu; Zhai, Jiwei; Liu, Xinyi; Lai, Tianshu; Song, Sannian; Song, Zhitang
Abstract: Superlattice-like Ge50 Te50 /Ge8 Sb92 (SLL GT/GS) thin film was systematically investigated for multi-level storage and ultra-fast switching phase-change memory application. In situ resistance measurement indicates that SLL GT/GS thin film exhibits two distinct resistance steps with elevated temperature. The thermal stability of the amorphous state and intermediate state were evaluated with the Kissinger and Arrhenius plots. The phase-structure evolution revealed that the amorphous SLL GT/GS thin film crystallized into rhombohedral Sb phase first, then the rhombohedral GeTe phase. The microstructure, layered structure, and interface stability of SLL GT/GS thin film was confirmed by using transmission electron microscopy. The transition speed of crystallization and amorphization was measured by the picosecond laser pump-probe system. The volume variation during the crystallization was obtained from x-ray reflectivity. Phase-change memory (PCM) cells based on SLL GT/GS thin film were fabricated to verify the multi-level switching under an electrical pulse as short as 30 ns. These results illustrate that the SLL GT/GS thin film has great potentiality in high-density and high-speed PCM applications.